Social and pedagogical work with children and youth in education institutions of territorial communities during marital state - Opanasenko Oksana (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2024)
The article defines the relevance of the problem of socio-pedagogical work with children and youth in educational institutions of territorial communities during the martial law. The social support system in Ukraine is highlighted, the importance of socio-pedagogical work with children and youth at the territorial community level in the context of war is analyzed, because children and youth are one of the most vulnerable social groups that need help and support in various aspects of their lives. The purpose of the article is to reveal the features of socio-pedagogical support for children and youth as participants in the educational process under martial law, to highlight the content of socio-pedagogical support in general secondary education institutions for children and youth, including internally displaced persons; analyze the role of a social educator in the community during martial law. Achieving the goal of the article enabled the use of general scientific methods: analysis of scientific and theoretical sources on the research problem, included observation, oral and written survey, methods of statistical data processing. It was noted that now socio-pedagogical work in various social institutes, ethnic and territorial communities is gaining more and more importance, in connection with this, the role of the social pedagogue in communities is increasing. The main purpose of the activity of a social pedagogue is characterized – creation of favorable conditions for adaptation and socialization of students, their personal development, prevention of negative phenomena among children with the help of interactive forms and methods of work; socio-pedagogical support in educational institutions for children and school youth in conditions of martial law, as they are in a state of stress due to constant alarms and shelling. The content of socio-pedagogical support for children, school youth of the community is outlined and the main areas of activity of a social pedagogue with children under martial law conditions are defined: socio-pedagogical diagnostics, social prevention, counseling, socio-pedagogical correction, rehabilitation activities.